Self-assembled peptide and protein nanostructures for anti-cancer therapy: Targeted delivery, stimuli-responsive devices and immunotherapy. (June 2021) - Delfi, Masoud; Sartorius, Rossella; Ashrafizadeh, Milad; Sharifi, Esmaeel; Zhang, Yapei; De Berardinis, Piergiuseppe; Zarrabi, Ali; Varma, Rajender S.; Tay, Franklin R.; Smith, Bryan Ronain; Makvandi, Pooyan
Highlights: Self-assembled peptide and protein nanostructures deliver therapeutics to cancer cells. Stimuli-responsive nanoarchitectures of peptide/protein respond to tumor microenvironment. Self-assembled peptide and protein nanomaterials are employed for cancer therapy. Virus-like nanoparticles are used for immunotherapeutic approaches. Graphical Abstract: Functionalized, self-assembled peptide and protein nanostructures encapsulate therapeutic agents for targeted cancer therapy. ga1 Abstract: Self-assembled peptides and proteins possess tremendous potential as targeted drug delivery systems and key applications of these well-defined nanostructures reside in anti-cancer therapy. Peptides and proteins can self-assemble into nanostructures of diverse sizes and shapes in response to changing environmental conditions such as pH, temperature, ionic strength, as well as host and guest molecular interactions; their countless benefits include good biocompatibility and high loading capacity for hydrophobic and hydrophilic drugs. These self-assembled nanomaterials can be adorned with functional moieties to specifically target tumor cells. Stimuli-responsive features can also be incorporated with respect to the tumor microenvironment. This review sheds light on the growing interest in self-assembled peptides and proteins and their burgeoning applications in cancer treatment and immunotherapy.